Pilipino translation of selected stories for story reading to children in the lower primary grades - Nunez, Nemah Castillo 1948-
Ten-story translations of animal stories which are meant to be read or told to children in the lower primary grades was the concern of this study with the following ends in view: to stimulate critical and creative thinking and to develop a genuine love for reading. Each story translation is accompanied by a set of discussion questions designed to help achieve the mentioned objectives.